PENGARUH LOKASI, PRODUK DAN HARGA TERHADAP MINAT BELI KONSUMEN UD. SUMBER REJO KABUPATEN MALANG - Muhammad Syahrul Wafa; Nur Hidayati; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study entitled the effect of location, product and price on consumer buying interest in UD. Sumber Rejo Malang. This research raises the problem of how location, product and price influence buying interest. This study aims to determine the effect of location, product and price on purchase intention. The population of this study were all customers of Sumber Rejo Building Depo, with the number of correspondents in June 2020 as many as 1800 respondents. Sampling using the Acidental Sampling method and a total sample of 95 people. This study uses multiple linear regression models. In this study, it shows that location, product and price simultaneously influence buying interest. Location has a significant positive effect on buying interest. Products have a significant positive effect on purchase intention. price has a significant positive effect on interest. Keywords: Location, Products and Prices and Buying Interest.